Reticulocytosis in non‐anaemic cats and dogs. (30th March 2018) - Fuchs, J.; Moritz, A.; Grußendorf, E.; Lechner, J.; Neuerer, F.; Nickel, R.; Rieker, T.; Schwedes, C.; DeNicola, D. B.; Russell, J.; Bauer, N.
Abstract : Objective: To evaluate the proportion of blood samples diagnosed with reticulocytosis without anaemia in cats and dogs and report the aetiology and mortality rate of affected animals. Materials and Methods: Retrospective multicentre study including haematological examination of 3956 cats and 11, 087 dogs admitted to seven German veterinary clinics (2012 to 2014). The proportion of blood samples with reticulocytosis without anaemia was calculated, and after exclusion of multiple measurements of the same animal, clinical data were evaluated. Animals with reticulocytosis without anaemia were classified as healthy or diseased, and diseased patients were assigned to 12 disease groups. Pretreatment ( i.e . non‐steroidal anti‐inflammatory drugs, glucocorticoids, dipyrone) was recorded. Results: The proportion of blood samples with reticulocytosis without anaemia was 3·1% (124/3956) in cats and 4·4% (492/11, 087) in dogs. Overall, 1·8% (2/111) of cats and 1·5% (7/458) of dogs with reticulocytosis without anaemia were healthy. Blood loss/anaemia, cardiac/respiratory disorders, gastrointestinal disorders and inflammatory disorders as well as cancer were the most frequent underlying diseases. Pretreatment was noted in 39·5% (43/111) of cats and 42·4% (194/458) of dogs. The mortality rate was 37·8% (42/111) in cats and 29·7% (136/458) in dogs with reticulocytosis without anaemia; the median survival time in non‐survivors was 1 day (range: 0 to 376 days in cats, 0 to 444 days in dogs). Clinical Significance: In both species, reticulocytosis without anaemia was observed in a low proportion of blood samples (dogs>cat). Though a bias towards sick animals is possible in our sample, reticulocytosis without anaemia was mainly seen in diseased animals and associated with a mortality rate of approximately one‐third of patients.